Improving The Teaching Capacity Of Vinh Long University Of Technology Education (Journal of Namibian Studies : History Politics Culture, 2023)
The vigorous development of science and technology has brought opportunities and posed significant challenges for lecturers, requiring them to have the necessary information technology application and communication competencies in all research and teaching activities. The teaching staff has been increasing in both quantity and professional capacity. Knowledge, professional qualifications, and practical capacity have been gradually improved in all aspects, positively contributing to the success of the country's renovation in the past period. The rapid development of science and technology has dramatically affected higher education, requiring lecturers to have the necessary competencies to adapt to digital transformation in education. The research has identified six key competencies needed in the context of transforming the number of university lecturers such as: Ability to understand ICT and operate equipment; digital processing capacity and creativity in teaching; scientific research capacity based on ICT; collaborative communication capacity based on digital technology; capacity for security and safety in cyberspace; ability to apply digital skills. The research results show that the level of achievement in the teaching capacity of lecturers in the context of digital transformation is only good compared to the necessity. This study is the basis for proposing solutions for further studies to promote the capacity of lecturers to meet the needs of the digital transformation context.